STRATEGI GURU DALAM PENGUATAN KARAKTER PADA ANAK USIA DINI DI TK RATNA KUMARA SARI KELURAHAN TONJA DENPASAR - Eka Nilasari Ni Putu (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2021)
Character education is a means of preserving the morality of human life which has a very important role and function, especially for early childhood. Teachers as educators in schools have good and appropriate strategies in educating children to have values of noble character. The problems that will be discussed include what are the strategies, the obstacles faced and the efforts made by the teacher in overcoming the obstacles faced to strengthen the character of early childhood in Ratna Kumara Sari Kindergarten, Tonja Village, Denpasar? The purpose of this study is to describe the strategies used by teachers in strengthening the character of early childhood in Ratna Kumara Sari Kindergarten, Tonja Village, Denpasar. The theory used is the theory of moral intelligence from Lickona, behavioristic theory from John. B. Watson. This type of research is qualitative. The subjects of this study were the head of PAUD, homeroom teachers of group B, representatives of parents and children aged 5-6 years. The data collection methods were non-participant observation, unstructured interviews and literature. The data that has been collected was analyzed by using the descriptive qualitative analysis method with reduction steps, data presentation and conclusion drawing. The results of the study stated that the results showed (1) the teacher's strategy in strengthening the character of early childhood in Ratna Kumara Sari Kindergarten, namely by carrying out three stages consisting of the planning stage (Designing curriculum, semester programs, RPPM and RPPH), Implementation Stage (Strengthening grades). -value children's character through learning and habituation activities that have character values) and the Evaluation Stage (Conducting an assessment of the level of achievement of children's character development through assessment instruments) (2) The obstacles faced by teachers in strengthening the character of early childhood in Ratna Kumara Sari Kindergarten, namely teachers feel less than optimal in guiding and monitoring children's development, teacher limitations in developing activities and learning media during learning from home (BDR), parents' delays in collecting documentation of children's learning outcomes and changes in behavior and decreased interest in children's learning when studying from home (3) The efforts made by the teacher to overcome the obstacles faced in strengthening the character of early childhood in Ratna Kumara Sari Kindergarten are: by utilizing technological developments as communication tools and media so that learning activities continue to run well, designing learning activities that contain character education, using learning media tools that are easily available and establishing good communication and cooperation between teachers and parents.